REDUKSI BANJIR MENGGUNAKAN KOLAM RETENSI DI SUNGAI BAKALAN, KABUPATEN JEPARA - Sunu Ardhi Nugroho; Rintis Hadian; Adi Yusuf Muttaqien (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2019)
Abstract: Bakalan River in Jepara Regency is a river with extreme runoff category that often causes flooding that overflows into the river embankment. Flood are often referred to as disas-ters caused by three consecutive days of rain. But the flood analysis that ever happened due to rain 2 days in a row. To overcome the flood, one of the suggested alternatives is retarding ba-sin. This study aims to determine the maximum flood discharge based on repeat period of 5, 20, 50 years and 2-days maximum annual rain in Bakalan River, to know the deposit volume of retarding basin and flood reduction potential after retarding basin was made. Maximum flood discharge were calculated using synthetic hydrograph method (HSS) of Nakayasu and Gama I. The deposit volume of retarding basin and the flood reduction potential can be calculate from flood routing analysis result with HEC-RAS. Flood routing were performed at 46 cross section point (RS) under existing and with retarding basin condition. From the calculation, the maxi-mum flood discharge on repeat period of 5 year (Q5), 20 year (Q20), 50 year (Q50) and 2 day maximum annual rain (Q-2 daily) is 151.641 m3/s; 218.772 m3/sec; 279.463 m3/s and 361.832 m3/sec. Flood routing results indicate that in existing condition there are floods in RS 44 due to Q50 and Q-2 daily, so retarding basin is planned on right site of RS 44 with an area of 60.000 m2 and elevation of +17 m. With retarding basin, flood routing results indicate that the Bakalan River can accommodate maximum flood discharge with deposit volume of retarding basin for Q50 and Q-2 daily respectively 91.480 m3 and 199,890 m3. This volume is equivalent to the flood reduction potential respectively 12.23% and 22.24%. Abstrak: Sungai Bakalan di Kabupaten Jepara merupakan sungai dengan kategori kelas limpasan ekstrim sehingga sering menimbulkan banjir yang melimpas tanggul sungai. Banjir sering disebut sebagai bencana akibat hujan 3 hari berturutan. Namun analisis banjir yang pernah terjadi disebabkan hujan 2 hari berturutan. Untuk mengatasi banjir, salah satu alternatif yang disarankan adalah kolam retensi. Penelitian ini bertujuan untuk mengetahui debit banjir maksimum kala ulang 5, 20, 50 tahun dan 2 harian maksimum tahunan di Sungai Bakalan, mengetahui volume simpanan kolam retensi dan potensi penurunan banjir setelah dibuat kolam retensi. Debit banjir maksimum dihitung dengan metode hidrograf satuan sintetis (HSS) Nakayasu dan Gama I. Perhitungan volume simpanan dan potensi penurunan banjir didapatkan dari pengolahan hasil penelusuran banjir dengan HEC-RAS. Penelusuran banjir dilakukan di 46 titik potongan melintang (RS) pada kondisi eksisting dan dengan kolam retensi. Dari perhitungan, dihasilkan debit banjir maksimum kala ulang 5 tahun (Q5), 20 tahun (Q20), 50 tahun (Q50) dan 2 harian maksimum tahunan (Q-2 harian) berturut-turut sebesar 151,641 m3/dt; 218,772 m3/dt; 279,463 m3/dt dan 361,832 m3/dt. Hasil penelusuran banjir menunjukkan bahwa pada kondisi eksisting terjadi banjir di RS 44 akibat Q50 dan Q-2 harian sehingga direncanakan kolam retensi pada lokasi kanan RS 44 dengan luas 60.000 m2 dan elevasi +17 m. Dengan kolam retensi, hasil penelusuran banjir menunjukkan bahwa Sungai Bakalan dapat menampung debit banjir maksimum dengan volume simpanan kolam retensi untuk Q50 dan Q-2 harian berturut-turut sebesar 91.480 m3 dan 199.890 m3. Volume ini setara dengan penurunan banjir masing-masing 12,23% dan 22,24%.